ANALISIS SWOT SEBAGAI UPAYA PENINGKATAN KINERJA PENGAWASAN APARAT INSPEKTORAT PROVINSI JAWA TENGAH - Sari, Maylia Pramono (Jurnal Dinamika Akuntansi, 2011)
Penelitian ini berusaha menyediakan peta keuntungan, kerugian, tantangan dan kesempatan yang berkaitan dengan kinerja inspektorat (Supervisory Board). Hasil dari penelitian ini adalah bahwa untuk meningkatkan kinerjanya, Inspectorat (Supervisory Board) bisa menerapkan 4 strategi yang tesedia pada matriks SWOT. Inspektorat (Supervisory Board) sebaiknya bisa mengatur kekuatan dan meminimalkan kelemahan yang dimiliki, memanfaatkan kesempatan yang berhubungan de-ngan tantangan dalam bentuk sumber daya manusia, anggaran, teknologi informasi dan struktur organisasi yang tepat.Ã‚Â This study attempts to provide mapping of the advantages, disadvantages, challenges, and opportunities associated with the performance of the Inspectorate (Supervisory Board). The results indicate that for improving the performance, the Inspectorate (Supervisory Board) of Central Java Province can apply one of the four strategies that are available on TOWS matrix above. The four strategies that can be selected are SO Strategy (Strengths-Opportunities), WO Strategy (Weakness-Opportunities), ST Strategy (Strengths-Threats), and WT Strategy (Weakness-Threats). It is suggested that for improving its performance, the Inspectorate (Supervisory Board) should be able to maintain power and minimize the weaknesses possessed; exploit opportunities and deal with the existing challenges in the form of HR, Budget, Information Technology, and proper Organizational Structure.